Methodology bases of studying relative’s expressed emotion towards individuals with chronic gastrointestinal diseases - Pastryk, Tetiana (Psychological Prospects Journal, 2022)
Purpose of the present study is to design a methodology of studying relative’s expressed emotion towards individuals with chronic gastrointestinal diseases based on modern theoretical models in public health.Methods of the study include the tools of theoretical analysis, in particular analysis, synthesis, generalization and systematization of the research data. Results demonstrate that biopsychosocial model, recovery model, and emotional distress model serve as methodology bases for the study of the relatives’ expressed emotion towards individuals with gastrointestinal diseases. Biomedical model is more popular and traditional in western countries. Biopsychosocial model takes into account the shortcomings of biomedical model thereby suggesting the treatment of illness and diseases as a result of simultaneous interaction of systems on the cellular, tissue, body, intrapersonal and interpersonal levels. The model integrates biological science with the individual unique features. It defines the extent of the interconnection between biological and psychosocial factors to explain illness, disease, and clinical data. The emotional distress model allows investigating the manifestation of emotional distress and its dynamics in individuals with gastrointestinal diseases related to the relatives’ expressed emotion towards these individuals. Conclusions. The reviewed models allowed elaborating the approaches to designing a methodology of studying the relatives’ expression emotion towards individuals with gastrointestinal diseases. Thus, the study of expressed emotion necessitates the use of these modern theoretical models and the selection of the respective psychodiagnostics tools. Among the prospects of further research are the application of biopsychological, recovery, and emotional distress models in improving life quality and well-being of individuals with gastrointestinal diseases.
Keywords: expressed emotion, chronic gastrointestinal diseases, biomedical model, biopsychosocial model, emotional distress pyramid, recovery model.